Implementasi Model Tikrar dalam Menghafal Al Qur’an di Asrama Umar bin Khattab Pondok Pesantren Muallimin Muhammadiyah Yogyakarta - Arvaddin Hamasy Al Qosam (PALAPA, 2023)
One model that is suitable as a solution for memorizing the Qur'an is the Tikrar Model. One model that is suitable as a solution for memorizing the Qur'an is the Tikrar Model. This pledge model is a model or way of memorizing the Qur'an by repeating the verses to be memorized. This study aims to explain the planning, implementation and results of using the Tikrar model in memorizing the Qur'an at the Muallimin Muhammadiyah Islamic Boarding School, Yogyakarta. This research is a field research with a qualitative approach. Data collection techniques using observation techniques, interviews and documentation. Data analysis in this study used three techniques, namely data reduction, data presentation and data conclusion. Data validity was checked by data triangulation with three modes, namely source triangulation, technical triangulation and time triangulation. The research process lasted for 5 months with research subjects, the Director of the Islamic Boarding School, Wadir IV Islamic Boarding School, KIS Affairs Staff, Pamong, Musyrif, Wali Santri, and Santri. While the object of research is regarding the use of the tikrar model in memorizing the Qur'an at the Umar bin Khattab Islamic Boarding School Mu'allimin Muhammadiyah Yogyakarta. The results of the study show that: (1) planning for the use of the tikrar model in memorizing the Qur'an is carried out with 3 things, namely, preparing Human Resources (HR) in this case is Musyrif as well as possible, then setting targets for memorization and providing appreciation for outstanding students in the field of Tahfidz Al-Qur'an. (2) during the implementation of the use of the Tikrar model in memorizing the Qur'an using technical students direct deposits to musyrifs, then the time is divided into 2, namely formal and non-formal. After that musyrif will report the students' memorization deposits to the system, by this system the achievements of the students' memorization deposits are sorted from the most to the fewest or commonly called the tahfidz league and there will also be monitoring and evaluation of the students' memorization deposits every once a week. (3) as for the results of using the Tikrar model in memorizing the Qur'an at the Umar bin Khattab Dormitory, out of a total of 188 students, there were a total of 153 students from the Umar bin Khattab Dormitory were able to complete their memorization targets, whereas in the form of a percentage as much as 81% of students completed the target of memorizing the Qur'an.